The importance of the study on emotions for pedagogical practice in early Childhood Education (Research, Society and Development, 2020)
This article aims to discuss the importance of emotions for pedagogical practice in early childhood education, since it is at this stage of children's development that we must pay attention to their emotional, social and educational development. Therefore, the work presents a methodology of bibliographic revision from books and articles that deal with the theme, to support the arguments presented by the authors of this article. The aim of the research is to direct a reflection on the kindergarten, which exists as a space for dialogue, exchange and knowledge construction, which consequently implies an educational practice intertwined with emotions, allowing the educational act to be based on love and hope, since emotions are responsible for the expressiveness and intensity with which things happen and develop. The results presented focus that the research on emotion is directed to the understanding of the homeless, entering the perception and look of each child and each teacher, because it is from the emotions that children build an image of themselves and the world. . Moreover, for pedagogical practice, knowledge about emotions leads to the need for a classroom that should be formed by people who carry a whole assumption of subjective formation, and that the search for enriching the memory of knowledge and significant truths, they lead to integral teacher and student training.